Pengenalan dan Pelatihan Aplikasi Scratch di SMP Negeri 5 Sambas Dalam Upaya Peningkatan Kemampuan Pemrograman Siswa di Bidang TIK - Heldi Hastriyandi; Hidayat, Andri; Wahyuni, Sri; Usman, Muhammad (Sehati Abdimas, 2024)
Based on data from the BPS of Sambas Regency, there was a significant increase of 0.85 points in the Human Development Index (HDI) in 2022, particularly in the education dimension. To maintain this momentum, it is essential to continuously improve the quality of education and the application of technology in the educational field. Through the integration of Computational Thinking (CT) into the curriculum, students are expected to gain a strong understanding of technology while enhancing the digital literacy of the younger generation. One of the methods used is the introduction of programming code using the Scratch application, which has been introduced at SMP Negeri 5 Sambas. However, this has primarily been in the form of theoretical module introduction, indicating a need for more practical experience rather than just theoretical knowledge to ensure a deeper understanding, especially considering the limitations of computer lab facilities. Politeknik Negeri Sambas plays a crucial role in preparing the younger generation to face digital literacy challenges by providing training and implementing the latest technologies, as directed through community service programs at SMP Negeri 5 Sambas. All these efforts aim to ensure that students are better prepared and competent to face the challenges and opportunities of the digital era.